PELATIHAN MENULIS DAN BAGIKAN KARYA DI WEB KOMPASIANA UNTUK DOSEN BARU DI FIP UNIVERSITAS NEGERI GORONTALO - Qaniah, Fadhilah Ahmad; Saldin, Muh; Khatimah, Khusnul (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
Writing on digital platforms is an important competency for lecturers to share ideas, experiences, and research findings with the wider community. One digital publication platform that can be utilized for this purpose is Kompasiana. This training is designed to improve the writing abilities of novice lecturers at the Faculty of Education (FIP), State University of Gorontalo, while also encouraging their participation in digital literacy. The implementation method includes three stages: (1) preparation of a pocket guide for writing on Kompasiana, (2) socialization, and (3) training with a blended learning approach that includes individual consultation sessions. The training focuses on hands-on practice and mentoring based on participants' needs. Thirteen articles were successfully published by participants on diverse themes, including education, classroom, socio-cultural sciences, and work-life. This result demonstrates the success of the training in facilitating lecturers to produce relevant content according to their fields of expertise. Practice-based training with individual mentoring has proven effective in enhancing lecturers' writing skills. The diversity of article themes reflects participants' ability to independently develop ideas. Recommendations for future research include expanding the participant scope with SEO optimization and evaluating the long-term impact on lecturers' academic productivity.